Evaluation of Hepatic Enzymes in major β-thalassemic Patients using Deferasirox - Dallal Bashi, Ahmed Yahya; Fathi, Fatimah Haitham (Iraqi Journal of Pharmaceutical Sciences, 2022)
Abstract β-thalassemia major is a genetic disease that causes sever defect in normal hemoglobin synthesis. The patients with β-thalassemia major need periodic blood transfusions that can result in accumulation of body iron, so treatment with iron chelating agent is required. Complications of this iron overload affecting many vital organs, including the liver. The aim of this work was to evaluate liver enzymes in β -thalassemia major patients with deferasirox versus without it. Two groups of β-thalassemia major patients were involved in this study named group A; 40 β-thalassemia patients of blood transfusion dependent without deferasirox, group B; 40 β-thalassemia patients of blood transfusion dependent on deferasirox. In addition to group C, 40 normal subjects as a control group. Samples of serum were obtained from all participants to be tested for alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase and ferritin. The biochemical data of the patients on blood transfusion without deferasirox showed significant increases in the mean serum levels of aminotransferases and ferritin in comparison with control. Whereas the patients on blood transfusion with deferasirox exhibit significant increases in the means serum levels of alkaline phosphatase activity and ferritin in comparison with control. Iron overload may cause liver injury, shown by significant increases of; ALT and AST activities and elevated ferritin level in serum of transfusion dependent patients of β-thalassemia major. Administration of deferasirox for β-thalassemia major patients causes elevation of serum ALP activity and ferritin level.